2020
DOI: 10.15218/ejnm.2020.08
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Levels of Hopelessness among the Patients with Major Depressive Disorder in Sulaimani City

Abstract: Background and Objectives: Major depressive disorder associated with greater morbidity and mortality. Many researchers have sought complex association between depressions with hopelessness. The level of severity of such factors can play role in the causes, recovery and prediction of depression. The main objective of this study is to assess the levels of hopelessness among patients with major depressive disorder. Methods: A quantitative descriptive study design was conducted at a psychiatric clinic in the Ali K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This result goes with the finding of (22,23) showed that women are 1.7 times more likely than men in lifetime history of major depressive disorder. In contrast, (24) found that the prevalence rate of males in community-based sample with major depressive disorder in city of Sulaimani. Furthermore, the study revealed that married females (75%) found to be considerably more prevalent to males (23%).…”
Section: Discussionmentioning
confidence: 78%
“…This result goes with the finding of (22,23) showed that women are 1.7 times more likely than men in lifetime history of major depressive disorder. In contrast, (24) found that the prevalence rate of males in community-based sample with major depressive disorder in city of Sulaimani. Furthermore, the study revealed that married females (75%) found to be considerably more prevalent to males (23%).…”
Section: Discussionmentioning
confidence: 78%